2012
DOI: 10.1038/nn.3021
|View full text |Cite
|
Sign up to set email alerts
|

Saccade-confounded image statistics explain visual crowding

Abstract: SUMMARY Processing of shape information in human peripheral visual fields is impeded beyond what can be expected by poorer spatial resolution. Visual crowding—the inability to identify objects in clutter—has been shown to be the primary factor limiting shape perception in peripheral vision. Despite the well documented effects of crowding, its underlying causes are poorly understood. Since spatial attention both facilitates learning of image statistics and directs saccadic eye movements, we propose that the acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 47 publications
(71 reference statements)
3
108
2
1
Order By: Relevance
“…Contrary to recent suggestions that crowding and saccades are closely linked (37)(38)(39), four aspects of our data lead us to reject an inextricable linkage between these processes. First, although crowding and saccades show similar patterns of variation, saccadic precision is worse in the lower visual field than in the upper-the opposite pattern not only to crowding, but also to a wide range of perceptual tasks (24,25).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to recent suggestions that crowding and saccades are closely linked (37)(38)(39), four aspects of our data lead us to reject an inextricable linkage between these processes. First, although crowding and saccades show similar patterns of variation, saccadic precision is worse in the lower visual field than in the upper-the opposite pattern not only to crowding, but also to a wide range of perceptual tasks (24,25).…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies suggest that there may be a particularly strong link between these processes (37)(38)(39), despite the more general dissociation between perceptual and saccadic localization (40)(41)(42)(43) and their apparently distinct cortical routes (34). Our first aim was therefore to examine whether saccadic precision and crowding covary across the visual field by measuring the size of crowded interference zones and the precision of saccade landing positions ("saccade error zones") for the same stimuli in a range of visual-field locations.…”
mentioning
confidence: 99%
“…Basic detectors signal the presence of the target (hence, target detection is not impaired). At the integration stage, feature location is lost since, for example, receptive fields are large and features are jumbled (Greenwood, Bex, & Dakin, 2009;Pelli et al, 2004) or inappropriate representations of image statistics are acquired due to saccade programming (Nandy & Tjan, 2012). In foveal vision, often lateral inhibition is proposed as a mechanism of interference by flankers (Westheimer & Hauske, 1975).…”
Section: Neural Mechanismsmentioning
confidence: 99%
“…Finally, the zone of crowding is not circular but, instead, exhibits a radialtangential anisotropy, such that flankers positioned along the radial axis from the fovea to the target will produce more crowding than those placed tangentially to this axis (Toet & Levi, 1992). Recently, Nandy and Tjan (2012) showed that all of these characteristics of crowding can be explained as a consequence of saccades confounding the statistics of natural images. However, identifying a central letter is very different from identifying a word.…”
Section: Intraword Spacing Effectsmentioning
confidence: 99%